Revisiting the physiological effects of exercise training on autonomic regulation and chemoreflex control in heart failure: does ejection fraction matter? - Andrade, David C.; Arce-Alvarez, Alexis; Toledo, Camilo; Diaz, Hugo S.; Lucero, Claudia; Quintanilla, Rodrigo A.; Schultz, Harold D.; Marcus, Noah J.; Amann, Markus; Del Rio, Rodrigo (My University, 2018)
Heart failure (HF) is a global public health problem that, independent of its etiology [reduced (HFrEF) or preserved ejection fraction (HFpEF)], is characterized by functional impairments of cardiac function, chemoreflex hypersensitivity, baroreflex sensitivity (BRS) impairment, and abnormal autonomic regulation, all of which contribute to increased morbidity and mortality. Exercise training (ExT) has been identified as a nonpharmacological therapy capable of restoring normal autonomic function and improving survival in patients with HFrEF. Improvements in autonomic function after ExT are correlated with restoration of normal peripheral chemoreflex sensitivity and BRS in HFrEF. To date, few studies have addressed the effects of ExT on chemoreflex control, BRS, and cardiac autonomic control in HFpEF; however, there are some studies that have suggested that ExT has a beneficial effect on cardiac autonomic control. The beneficial effects of ExT on cardiac function and autonomic control in HF may have important implications for functional capacity in addition to their obvious importance to survival. Recent studies have suggested that the peripheral chemoreflex may also play an important role in attenuating exercise intolerance in HFrEF patients. The role of the central/peripheral chemoreflex, if any, in mediating exercise intolerance in HFpEF has not been investigated. The present review focuses on recent studies that address primary pathophysiological mechanisms of HF (HFrEF and HFpEF) and the potential avenues by which ExT exerts its beneficial effects.
Keywords: autonomic control; chemoreflex drive; exercise training; heart failure